Cytokine profile in the peripheral blood and the brain in patients with focal drug-resistant epilepsy - D. A. Sitovskaia; A. V. Litovchenko; E. D. Bazhanova; E. N. Skiteva; Yu. M. Zabrodskaia (Сеченовский вестник)
Aim. To study markers of blood-brain barrier dysfunction (BBB) in patients with pharmacoresistant epilepsy (PhRE) – the amount of VEGF in endotheliocytes of brain capillaries, TNF-α in brain tissue and cytokine profile in blood serum.Materials and methods. The study included 30 patients with PhRE who underwent anterior temporal bloc resection. Histological samples of the brain were examined to assess the amount of VEGF and TNF-α; the concentration of cytokines in the blood serum was determined.Results. In the PhRE group, the densitometric density of cells expressing VEGF and the amount of TNF-α in the epileptogenic focus were higher than in the control groups (p < 0.001; p < 0.05). Compared with the control, the serum concentrations of IL-2 (0.98 ± 0.28 pg/ml vs. 2.80 ± 0.71 pg/ml; p < 0.001), IL-8 (14.04 ± 1.46 pg/ml vs. 26.13 ± 3.80 pg/ml; p < 0.001) and EGF (43.72 ± 5.63 pg/ml vs. 83.62 ± 24.06 pg/ml; p < 0.05) were statistically significantly lower in the PhRE group, and the amount of TNF-α (33.09 ± 1.23 pg/ml vs. 24.85 ± 1.32 pg/ml, p < 0.05), IL-4 (43.73 ± 2.57 pg/ml vs. 32.37 ± 5.80 pg/ml, p < 0.05), IL-5 (43.73 ± 2.57 pg/ml vs. 32.37 ± 5.80 pg/ml; p < 0.05), IL-7 (16.65 ± 3.07 pg/ml vs. 8.13 ± 1.67 pg/ml; p < 0.05), GRO (growth-regulated protein) (3054.0 ± 200.8 pg/ml vs. 1367.0 ± 187.3 pg/ml; p < 0.001), VEGF (316.10 ± 55.28 pg/ml vs. 95.22 ± 15.78 pg/ml; p < 0.01) are statistically significantly higher. There were no significant differences in the concentration of IL-1β, IL-1RA, IL-10 and IFN-γ between the PhRE group and the control.Conclusion. Based on the studied cytokine profile, there is no systemic inflammation in patients with PhRE. The established overexpression of VEGF in the brain and an increase in its concentration in the blood, combined with a decrease in serum EGF concentrations and an increase in GRO, as well as pro-inflammatory factors, indicates damage to the BBB. A high amount of TNF-α in the epileptic focus indicates neuroinflammation, and an increased concentration of this marker can be found in the blood of patients with BBB dysfunction.